PENINGKATAN KAPASITAS GURU TERHADAP PENGGUNAAN GAMIFIKASI BERBASIS ZEPQUIZ UNTUK MENINGKATKAN EFESIENSI DAN KUALITAS PEMBELAJARAN - Agustan Syamsuddin; Hamdana Hamading; Septianingsih; Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT The integration of digital technology in learning requires teachers to have competencies in utilizing innovative and interactive instructional media. One effective approach is gamification, which has been proven to enhance students’ motivation, engagement, and learning quality. However, preliminary observations indicated that teachers at SD Negeri Lanto Passewang had limited experience in implementing gamification-based learning and were unfamiliar with the ZepQuiz application. Therefore, this Community Service Program (PKM) aimed to improve teachers’ capacity in using gamification supported by the ZepQuiz application to enhance learning efficiency and quality. The program was implemented through planning, implementation, and reporting stages using training, hands-on practice, and mentoring methods involving all teachers at the school. The results showed an improvement in teachers’ understanding and skills in designing and implementing interactive gamified quizzes. The use of ZepQuiz increased learning efficiency through automatic assessment and improved learning quality by creating a more interactive and engaging learning environment. Thus, gamification supported by ZepQuiz can serve as an effective instructional strategy in elementary schools.